2017
DOI: 10.1098/rsos.160561
|View full text |Cite
|
Sign up to set email alerts
|

Modelling human perception processes in pedestrian dynamics: a hybrid approach

Abstract: In this paper, we present a hybrid mathematical model describing crowd dynamics. More specifically, our approach is based on the well-established Helbing-like discrete model, where each pedestrian is individually represented as a dimensionless point and set to move in order to reach a target destination, with deviations deriving from both physical and social forces. In particular, physical forces account for interpersonal collisions, whereas social components include the individual desire to remain sufficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A further model improvement can be represented by the inclusion of bee gazing direction as a further degree of freedom. In this respect, as done in the case of pedestrians [15], for each insect i, it should be defined a unit vector, say g i (t) = (cos γ i (t), sin γ i (t)) (being γ i the angle between g i itself and the x-axis of the domain), defining the direction of its gaze, cf. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A further model improvement can be represented by the inclusion of bee gazing direction as a further degree of freedom. In this respect, as done in the case of pedestrians [15], for each insect i, it should be defined a unit vector, say g i (t) = (cos γ i (t), sin γ i (t)) (being γ i the angle between g i itself and the x-axis of the domain), defining the direction of its gaze, cf. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Participants tended to pass behind when they looked at the interferer early in the interaction and when the duration of the fixation was long. It has even been shown that people use the gaze behavior of others to adjust their behavior (Dicks, Clashing, O'Reilly, & Mills, 2016;Colombi, Scianna, & Alaia, 2016;Colombi & Scianna, 2017), likely because it informs about the action intentions. Therefore, we focus on understanding how a person interacts with its environment based on its gaze activity.…”
Section: Introductionmentioning
confidence: 99%
“…This social component can also be modeled mathematically. For example, Colombi and Scianna ( 2017 ) made a first attempt to include the subjective perception of the attractor-state of multiple persons in their model. Although the model did not expand on an agent's action opportunities, it did report the that subjective perception influenced sequential (i.e., localized perception) and simultaneous (i.e., distributed perception) interactions.…”
Section: Discussionmentioning
confidence: 99%